Lung cancer after lung transplantation: An analysis of 25 years of experience in a single institution. Issue 1 (5th December 2018) - Chatron, Eva; Dégot, Tristan; Salvaterra, Elena; Dumazet, Antoine; Porzio, Michele; Hirschi, Sandrine; Schuller, Armelle; Massard, Gilbert; Renaud‐Picard, Benjamin; Kessler, Romain
Abstract: Background: The aim of our study was to describe the lung cancer characteristics in lung transplant recipients at our institution. Methods: Between January 1, 1992, and August 15, 2017, 463 patients underwent lung transplantation. Results: We found a total of 19 lung cancers (4.10%). Eight patients had lung cancer in the explanted lung, 8 in the native remaining lung, and 3 in the transplanted lung. Histopathological findings were: adenocarcinoma in 10, SCC in 8 patients, and 1 was undetermined. Among lung cancers in the explanted lungs, there were 6 stage I, 1 stage III, 1 stage IV. Among patients with a lung cancer in the remaining native lung, 3 had early stage disease and 5 had stage IV disease. Among lung cancers in the transplanted lung, there were: 1 stage I, 1 stage II and 1 stage IV. Overall median survival in lung transplant recipients without lung cancer was 8.77 ± 0.74 years compared to 6.19 ± 1.4 years in recipients with lung cancer. Conclusion: Lung cancer following lung transplantation was uncommon. Early stage lung cancer discovered in the explanted lungs had no impact on survival. Lung cancer occurring in the transplanted or in the native remaining lung had a poor prognosis.